Wasted Heat Engine Utilization in Central AC Condenser Type Water Chiller for Economical Energy Water Heaters - Rasta, I Made (Jurnal Energi Dan Manufaktur; Vol 3, No.2 Oktober 2009, 2012)
Central AC type water chiller is a refrigeration machine that release heat to environment. Heat energy that released to environment comes from room heat load that absorbed by machine and heat from compressor. The best form in using this loss energy is heat recovery water heater technology, where this machine will take heat from condenser by a heat exchanger to heating water. Refrigerant will flow in the heat exchanger before entering condenser, after that refrigerant flow to other components such as, expansion valve, evaporator, compressor and than return again to condenser, this process will be cycling regularly (closed cycle). Based on experimental and analysis result especially for AC with capacity 2 Pk, and tank capacity 75 liter, with water heater recovery device obtained that: (1) Compressor power consumption decrease from 1.66 kW to 1.59kW. (2) Heat rejected from condenser and used by water heater has ratio 4.683 kJ/s and 1.59 kJ/s, with water heater efficiency is 32.2%. (3) Maximum water temperature can be reached are in range 34oC – 47.5oC in 10-150 minutes and flow rate is 0.5 – 2.5 liter /min
Keywords: AC, Refrigerant, Heat and Water heater